The System of Theoretical Pressupositions and Concepts in Jeffrey Alexander’s Sociology. Distinctive Features of Neofunctionalism - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to analyze the conceptual system neo-functionalist sociology, central to which are the ideas of Jeffrey Alexander. One of the main qualities of this project is its multidimensional scope and the attempts to link theoretical considerations with the substantive analyses. The multidimensional character of the project connects Alexander’s neo-functionalism with the works of authors like P. Colomy, R. Munch and provides the grounds for social theorizing that is attentive to the processes of differentiation, which generate changes in social, cultural and personality systems.